Projeto Ético-Político do Serviço Social brasileiro: uma análise sobre a sua produção teórica na contemporaneidade - Santos, Edson dos (2019)
The present dissertation had as object of investigation the current Ethical-Political Project of the Brazilian Social Work, considering that this is the product of the struggles that were being fought in Latin America by the working class of several professional categories; social movements; labor unions that influenced part of the professional category of social workers dissatisfied with the conservative profile of the profession. The general objective was to analyze the theoretical-methodological dimension of Social Work in the context of publications on the contemporary ethical-political project that characterize part of its materialization. For this, it was established as specific objectives: a) problematize the genesis of the current ethical-political project of the Brazilian Social Service, rescuing the debate about its hegemony and crisis; b) carry out a bibliographic survey on the production of Social Work knowledge about the ethical-political project in contemporary times; c) analyze the theoretical production of Social Work about the professional project about the consolidation of the ethical-political project of the profession. It was based on the understanding that it is necessary to deepen the debate on the professional project of Social Work in contemporary times, since it is observed that although the theoretical publications on it have increased, it is noted that the quantity of these publications is still small. The research was of the bibliographic type and of quantitative and qualitative nature, being guided by dialectical materialism, which enables the movement of successive approximations between subject-object. The empirical field of study and research sources was the theoretical production in the area of Social Work, resulting from scientific articles published between the years 2016 to 2018. As for the universe of research, a bibliometric research on the publications on the theme of the ethical-political project of the profession in the magazines Katálysis and Social Work & Society available on the SciElo website that had the keywords: Social Work; "social issues"; ethical-political project of the Brazilian Social Work; Marxism; hegemony and (neo) conservatism. This survey resulted in a total of 133 articles that approached the research object, which resulted in a sample of 41 articles, after applying the criterion for verifying the most repeated keywords in the abstracts, since in the total of the research universe. such keywords appeared at least once in each job. The bibliographic research made possible to elaborate considerations about the discussion of the materialization of the PEP; perform a mapping of the higher education institutions that most produced knowledge about the object of this study; visualize that the practice of research and production of knowledge of Social Work continues to occur more frequently through professionals inserted in academic spaces, as well as the low production / publication of studies on the theme of PEP and its materialization, reinforcing the need to deepen the debate about the materialization and hegemony of the professional project.